The music in the fairy queen : English opera (1692) Vocal score The drama adapted from a midsummer night's dream by shakespeare - PURCELL, Henry (Novello & Co. Ltd, 1966)
PreludenHornpipenAirnRondeaunDuet (Soprano & bass) come let us leave the town